Stress-induced electronic structure modulation of manganese-incorporated Ni2P leading to enhanced activity for water splitting - Sarkar, Shreya; Dheer, Lakshay; Vinod, C. P.; Thapa, Ranjit; Waghmare, V. Umesh; Peter, Sebastian C. (ACS Applied Energy Materials, 2020)
The cornerstone of the emerging hydrogen economy is hydrogen production by water electrolysis with concomitant oxygen generation. Incorporating a third element in metal phosphides can tune the crystalline and electronic structure, hence improving the electrocatalytic properties. In this work, Mn-doped Ni2P with varying ratios of Mn and Ni has been explored as excellent catalysts for water splitting. A complete cell made of the best catalyst Ni1.5Mn0.5P electrodes showed low voltage of 1.75 V at a current density of 10 mA cm(-2) due to enhanced electrical conductivity, induction of tensile stress, enhanced electrochemical surface area, and increased electric dipole upon Mn incorporation.
Keywords: Electronic Structure; hydrogen evolution reaction; Oxygen Evolution Reaction; phosphides; water splitting

Operando generated ordered heterogeneous catalyst for the selective conversion of CO2 to methanol - Cherevotan, Arjun; Raj, Jithu; Dheer, Lakshay; Roy, Soumyabrata; Sarkar, Shreya; Das, Risov; Vinod, Chathakudath P.; Xu, Shaojun; Wells, Peter; Waghmare, V, Umesh; Peter, Sebastian C. (ACS Energy Letters, 2021)
The discovery of new materials for efficient transformation of carbon dioxide (CO2) into desired fuel can revolutionize large-scale renewable energy storage and mitigate environmental damage due to carbon emissions. In this work, we discovered an operando generated stable Ni-In kinetic phase that selectively converts CO2 to methanol (CTM) at low pressure compared to the state-of-the-art materials. The catalytic nature of a well-known methanation catalyst, nickel, has been tuned with the introduction of inactive indium, which enhances the CTM process. The remarkable change in the mechanistic pathways toward methanol production has been mapped by operando diffuse reflectance infrared Fourier transform spectroscopy analysis, corroborated by first-principles calculations. The ordered arrangement and pronounced electronegativity difference between metals are attributed to the complete shift in mechanism. The approach and findings of this work provide a unique advance toward the next-generation catalyst discovery for going beyond the state-of-the-art in CO2 reduction technologies.